The Effectiveness of Playing Ball Stimulation to the Gross Motor Development of 24-36 months Children - Maria Ulfa; Laily Prima Monica; Wahyu Wibisono (STIKes Patria Husada Blitar, 2019)
Various research results reveal that early age is a golden period for the development of children in which 50% of the intelligence development occurs at the age of 0-4 years and 30% in the following 8 years. Early childhood education also needs to be considered since education plays an important role in the process of growth and development of the children. The purpose of this study was to determine the effectiveness of playing ball stimulation to the gross motor development in children aged 24-36 months.This study used a pre-experimental design with posttest only control group design. The population was 150 children in all Posyandu in the working areas of the PKM Kanigoro. The sampling technique used purposive sampling. The independent variable was playing ball stimulation, while the dependent variable was gross motor development. The instrument used KPSP.The results of Wilcoxon Signed Rank statistical test showed p = 0.005 (Î± = 0.05), indicated that playing ball stimulation could improve gross motor skills development of children. It is expected that the parents of the respondents more active in asking questions, watching carefully on how to provide stimulation to the children, especially in stimulating ball games, so that it could help them in increasing their children gross motor skills. The results of this study can also be used as an input for health workers to further improvement of counseling during posyandu activities, so that the gross motor development of children continues to increase well.